Gelatin Methacryloyl‐Based Tactile Sensors for Medical Wearables. (6th September 2020) - Li, Zhikang; Zhang, Shiming; Chen, Yihang; Ling, Haonan; Zhao, Libo; Luo, Guoxi; Wang, Xiaochen; Hartel, Martin C.; Liu, Hao; Xue, Yumeng; Haghniaz, Reihaneh; Lee, KangJu; et al.
Abstract: Gelatin methacryloyl (GelMA) is a widely used hydrogel with skin‐derived gelatin acting as the main constituent. However, GelMA has not been used in the development of wearable biosensors, which are emerging devices that enable personalized healthcare monitoring. This work highlights the potential of GelMA for wearable biosensing applications by demonstrating a fully solution‐processable and transparent capacitive tactile sensor with microstructured GelMA as the core dielectric layer. A robust chemical bonding and a reliable encapsulation approach are introduced to overcome detachment and water‐evaporation issues in hydrogel biosensors. The resultant GelMA tactile sensor shows a high‐pressure sensitivity of 0.19 kPa −1 and one order of magnitude lower limit of detection (0.1 Pa) compared to previous hydrogel pressure sensors owing to its excellent mechanical and electrical properties (dielectric constant). Furthermore, it shows durability up to 3000 test cycles because of tough chemical bonding, and long‐term stability of 3 days due to the inclusion of an encapsulation layer, which prevents water evaporation (80% water content). Successful monitoring of various human physiological and motion signals demonstrates the potential of these GelMA tactile sensors for wearable biosensing applications. Abstract : Skin bioelectronics is developed from GelMA hydrogel, enabling its active interfacing with the human body. The GelMA hydrogel biosensor is skin‐conformable, biocompatible, transparent, and developed with fully solution‐processable techniques. Excellent durability and long‐term stability are realized by interface‐engineering and encapsulation.